ANALYSIS OF THE READINESS AND ACCEPTANCE OF TECHNOLOGY BY ACEH PATCHOULI FARMERS IN AGRIBUSINESS DEVELOPMENT USING THE "MYNILAM" ERP WITH THE TRAM MODEL IN PATCHOULI FARMING GROUPS IN ACEH - Adinda Gusti Vonna; Nova Suryani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The "MyNilam" ERP system was developed as an integrated digital solution to improve the efficiency and transparency of patchouli commodity management in Aceh. However, its successful implementation is highly dependent on user readiness and acceptance. This study aims to analyze the readiness of patchouli farmers and industry players to use the "MyNilam" ERP using the Technology Readiness and Acceptance Model (TRAM). This literature study highlights previous research related to ERP technology readiness in the last 5 years and provides a theoretical basis for future field studies. Findings from the literature indicate that discomfort and perceived ease of use are the key variables that most influence ERP adoption in various industrial sectors in Indonesia.